Pengembangan Teknologi Realitas Tertambah Sebagai Media Pembelajaran Pengenalan Jenis Gigi Makhluk Hidup Berbasis Android - Geovanta Riswan Siswanto; Paramaresthi Windriyani (UNIVERSITAS KALBIS, 2022)
The purpose of this study is to develop an alternative medium of learning the introduction of types of animal teeth in elementary school students using Augmented Reality technology. Augmented Reality is a technology where users can see objects in three dimensions (3D). The method used in the introduction of animal teeth type applications uses the Multimedia Development Life Cycle (MDLC). This method has six stages: concept, design, material collecting, assembly, testing, and distribution. For the development of animal tooth recognition applications using Unity with C # programming language. The result of this study is animal teeth type recognition application with the Android platform that can detect markers and display three types of animal teeth in three-dimensional (3D) objects, and there are rotational features, enlarge and reduce and information of each creatures teeth.